Predicting adverse outcomes in obstetric sepsis using modified sepsis scores - Amita Ray; Debjani Goswami; Bharath Kumar (Barpeta Obstetrics and Gynaecological Society, 2021)
Background: Obstetric sepsis continues to be one of the major causes of maternal mortality. Assessment of obstetric sepsis and management plans need to take into consideration the altered immunological and physiological responses of pregnancy. Obstetrically modified Sequential Organ Failure Assessment (omSOFA) and quick omSOFA (omqSOFA) scores have been proposed which take into account these altered responses. Objectives: We did this study with the objective of comparing the omSOFA and omqSOFA scores with the original SOFA and original quick SOFA (q-SOFA) scores to find which of these better predicted the outcomes of mortality, intensive care unit (ICU) stay and hospital stay in patients with obstetric sepsis. Materials and methods: All cases of obstetric sepsis admitted to our hospital ICU during the period August 2018 to July 2019 were included in this study. The SOFA scores, and the obstetrically modified SOFA scores were calculated, sepsis biomarkers send and all were assessed for their ability to predict mortality using binary logistic regression. Results: There was a significant association (p< 0.001) between mortality and the SOFA, om-SOFA and omq-SOFA scores. The q-SOFA score was not significantly associated with mortality (p value= 0.315). The om-SOFA proved to be the best predictor of mortality. Adding biomarkers to the calculations did not significantly improve the predictability of the om-SOFA score. Conclusion: Modifying the SOFA scores has increased the predictability of mortality in obstetric sepsis and these should be used when assessing and monitoring this special category of sepsis patients.